Evaluation of Drug‐Drug Interaction Liability for Buprenorphine Extended‐Release Monthly Injection Administered by Subcutaneous Route. Issue 9 (22nd March 2021) - Kharidia, Jahnavi; Howgate, Eleanor M.; Laffont, Celine M.; Liu, Yongzhen; Young, Malcolm A.
Abstract: Buprenorphine extended‐release (BUP‐XR) formulation is a once‐monthly subcutaneous injection for the treatment of opioid use disorder (OUD). Buprenorphine undergoes extensive cytochrome P450 (CYP) 3A4 metabolism, leading to potential drug‐drug interactions (DDIs) as reported for sublingual buprenorphine. Sublingual buprenorphine is subject to first‐pass extraction, as a significant proportion of the dose is swallowed. Because subcutaneous administration avoids first‐pass extraction, the DDI with CYP3A4 inhibitors is expected to be less than the 2‐fold increase reported for the sublingual route. The objective of this analysis was to predict the magnitude of DDI following coadministration of BUP‐XR with a strong CYP3A4 inhibitor or inducer using physiologically based pharmacokinetic (PBPK) modeling. Models were developed and verified by comparing predicted and observed data for buprenorphine following intravenous and sublingual dosing. Comparison of predicted and observed pharmacokinetic (PK) profiles and PK parameters demonstrated acceptable predictive performance of the models (within 1.5‐fold). Buprenorphine plasma concentrations following administration of a single dose of BUP‐XR (300 mg) were simulated using a series of intravenous infusions. Daily coadministration of strong CYP3A4 inhibitors with BUP‐XR predicted mild increases in buprenorphine exposures (AUC, 33%‐44%; Cmax, 17‐28%). Daily coadministration of a strong CYP3A4 inducer was also associated with mild decreases in buprenorphine AUC (28%) and Cmax (22%). In addition, the model predicted minimal increases in buprenorphine AUC (8%‐11%) under clinical conditions of 2 weeks' treatment with CYP3A4 inhibitors administered after initiation of BUP‐XR. In conclusion, the PBPK predictions indicate that coadministration of BUP‐XR with strong CYP3A4 inhibitors or inducers would not result in clinically meaningful interactions.